Women's Opportunities and Challenges in Sub-Saharan African Job Markets - Dieterich, Christine; Huang, Anni.; Thomas, Alun. (Washington, D.C. : International Monetary Fund, 2016)
As labor market data is scarce in Sub-Saharan Africa (SSA), this paper uses household survey data to analyze the determinants of the gender gap in the labor market and its welfare implications for five SSA countries in multinomial logit models with propensity score matching method. The analysis confirms that education opens up opportunities for women to escape agricultural feminization and engage in formal wage employment, but these opportunities diminish when women marry-a disadvantage increasingly relevant when countries develop and urbanization progresses. Opening a household enterprise offers women an alternative avenue to escape low-paid jobs in agriculture, but the increase in per capita income is lower than male-owned household enterprises. These findings underline that improving women's education needs to be supported by measures to allow married women to keep their jobs in the wage sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet